Purple mountain majesties : the story of Katharine Lee Bates and "America the Beautiful" - Younger, Barbara, 1954-; Schuett, Stacey (New York : Puffin, 2002)
A brief biography of the author and college professor whose travels across the United States inspired her to write the poem which became the song "America the Beautiful."
5.7
K-3
K-3
Wilson's Children
Elem. School Library Collection
School Library Journal
Keywords: Bates, Katharine Lee, -- 1859-1929 -- Juvenile literature; Women authors, American -- 19th century -- Biography -- Juvenile literature; Women authors, American -- 20th century -- Biography -- Juvenile literature; Bates, Katharine Lee, -- 1859-1929.; Authors, American; Women -- Biography; Bates, Katharine Lee, -- 1859-1929.; American authors -- Biography; Women -- Biography